2021
DOI: 10.1007/s00216-021-03505-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting targeted and untargeted approaches for the analysis of bacterial metabolites under altered growth conditions

Abstract: In the host, pathogenic microorganisms have developed stress responses to cope with constantly changing environments. Stress responses are directly related to changes in several metabolomic pathways, which could hamper microorganisms' unequivocal identification. We evaluated the effect of various in vitro stress conditions (acidic, basic, oxidative, ethanolic, and saline conditions) on the metabolism of Staphylococcus aureus, Bacillus cereus, and Pseudomonas aeruginosa, which are common lung pathogens. The met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“… 4 Likewise, figuring out the interaction between respiratory flora and host metabolites contributes to an explanation of the pathogenesis of respiratory diseases and leads to a breakthrough in treatment. 5 Analysis of respiratory microbial diversity, macrogenomics, and metabolomics in cystic fibrosis patients found unique combinations of bacterial genera and metabolites in different disease states and indicated that three additional exacerbations and treatments culminated in a new airway microbiome and metabolome. 6 However, the correlation between lower respiratory microbial diversity, P. aeruginosa infection, and host metabolites has not been thoroughly explained in bronchiectasis patients.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Likewise, figuring out the interaction between respiratory flora and host metabolites contributes to an explanation of the pathogenesis of respiratory diseases and leads to a breakthrough in treatment. 5 Analysis of respiratory microbial diversity, macrogenomics, and metabolomics in cystic fibrosis patients found unique combinations of bacterial genera and metabolites in different disease states and indicated that three additional exacerbations and treatments culminated in a new airway microbiome and metabolome. 6 However, the correlation between lower respiratory microbial diversity, P. aeruginosa infection, and host metabolites has not been thoroughly explained in bronchiectasis patients.…”
Section: Introductionmentioning
confidence: 99%